Development and Testing of a Low-Cost Water Level Sensor and a Mobile Based Real-time Flood Warning System for the Flash Flood Prone North Eastern Part of Bangladesh - Ahmed, Nova; Islam, Md. S.; Kalam, Sifat; Islam, Farzana; Chowdhury, Nabila; Hafiz, Raquebul Salman; Sadat, Nazmus; Tabassum, Rozana; Nahar, Nazmun; Mamtaz, Maisha; Ahmed, Shoaib (International Journal of Sensors Wireless Communications and Control, 2021)
Background: The North-Eastern part of Bangladesh suffers from frequent flash flood, causing colossal damage to life and properties, especially the vast croplands. A distributed sensing system can monitor the water level on a continuous basis to warn people near the riverbank beforehand and reduce the damage largely. However, the required communication infrastructure is not available in most of the remote rural areas in a developing country like Bangladesh. Objective: This study intends to develop a low-cost sensor-based warning system, customizing to the Bangladesh context. Methods: The system utilizes a low-cost ultrasound-based sensor device, a lightweight mobile phone-based server, low-cost IoT sensing nodes, and a central server for continuous monitoring of river stage data along with the provision of storage and long-term data analytics. Results: A flash flood warning system was developed afterward with the sensors, mobile-based server, and appropriate web-based interfaces. The device was tested for some environmental conditions in the lab and deployed later in the outdoor conditions for short-term periods. Conclusion: Overall, the warning system performed well in the lab as well as in the outdoor environment, with the ability to detect water level at reasonable accuracy and transmit data to the server in real time. Some minor shortcomings were still noted with the scope for improvements, which are in the way to improve further.
Keywords: water level detection